Role of Adenoviruses in Cancer Therapy - Tseha, Sintayehu Tsegaye (Frontiers in Oncology, 2022)
Cancer is one of the leading causes of death in the world, which is the second after heart diseases. Adenoviruses (Ads) have become the promise of new therapeutic strategy for cancer treatment. The objective of this review is to discuss current advances in the applications of adenoviral vectors in cancer therapy. Adenoviral vectors can be engineered in different ways so as to change the tumor microenvironment from cold tumor to hot tumor, including; 1. by modifying Ads to deliver transgenes that codes for tumor suppressor gene (p53) and other proteins whose expression result in cell cycle arrest 2. Ads can also be modified to express tumor specific antigens, cytokines, and other immune-modulatory molecules. The other strategy to use Ads in cancer therapy is to use oncolytic adenoviruses, which directly kills tumor cells. Gendicine and Advexin are replication-defective recombinant human p53 adenoviral vectors that have been shown to be effective against several types of cancer. Gendicine was approved for treatment of squamous cell carcinoma of the head and neck by the Chinese Food and Drug Administration (FDA) agency in 2003 as a first-ever gene therapy product. Oncorine and ONYX-015 are oncolytic adenoviral vectors that have been shown to be effective against some types of cancer. The Chiness FDA agency has also approved Oncorin for the treatment of head and neck cancer. Ads that were engineered to express immune-stimulatory cytokines and other immune-modulatory molecules such as TNF-α, IL-2, BiTE, CD40L, 4-1BBL, GM-CSF, and IFN have shown promising outcome in treatment of cancer. Ads can also improve therapeutic efficacy of immune checkpoint inhibitors and adoptive cell therapy (Chimeric Antigen Receptor T Cells). In addition, different replication-deficient adenoviral vectors (Ad5-CEA, Ad5-PSA, Ad-E6E7, ChAdOx1–MVA and Ad-transduced Dendritic cells) that were tested as anticancer vaccines have been demonstrated to induce strong antitumor immune response. However, the use of adenoviral vectors in gene therapy is limited by several factors such as pre-existing immunity to adenoviral vectors and high immunogenicity of the viruses. Thus, innovative strategies must be continually developed so as to overcome the obstacles of using adenoviral vectors in gene therapy.